2020
DOI: 10.1021/acsenergylett.0c01401
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Design of Graphite-Compatible Electrolytes in Potassium-Ion Batteries

Abstract: Potassium ion batteries (KIBs) are attractive alternatives to lithium-ion batteries (LIBs) due to their lower cost and global potassium sustainability. However, designing compatible electrolytes with the graphite anode remains challenging. This is because the electrolyte decomposition and/or graphite exfoliation (due to K + -solvent co-insertion) always exist, which is much harder to overcome compared to the case of LIBs due to the higher activities of K + . Herein, we report a general principle to design comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 81 publications
0
91
1
Order By: Relevance
“…Furthermore, when PANa binder is used, an influence of different electrolyte salts of KFSA, KTFSA, and KPF6 appears to be insignificant (Figure S9). We note that a solution of 1.0 mol dm -3 KFSA/EC:DEC still offers higher initial Coulombic efficiency and cycle stability compared to 0.8 mol dm -3 KPF6/EC:DEC. 25 Additionally, an influence of EC-based binary solvents of EC:DEC, EC:DMC, and EC:PC on the reversibility is negligible for the PANa electrode during 100 cycles as confirmed by Figure S10, but 1.0 mol dm -3 KFSA/PC results in continuous electrolyte decomposition at 0.7 V vs. K (equal to 0.8 V vs. Li), which is likely due to co-intercalation of PC-solvated K + ions and/or dissolution of SEI components, leading to graphite exfoliation and electrolyte decomposition 24 similar to Li|LiClO4-PC|graphite cell. [30][31][32] Thus, we selected an electrolyte of 1.0 mol dm -3 KFSA/EC:DEC for the subsequent studies.…”
Section: Electrochemical Propertiesmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, when PANa binder is used, an influence of different electrolyte salts of KFSA, KTFSA, and KPF6 appears to be insignificant (Figure S9). We note that a solution of 1.0 mol dm -3 KFSA/EC:DEC still offers higher initial Coulombic efficiency and cycle stability compared to 0.8 mol dm -3 KPF6/EC:DEC. 25 Additionally, an influence of EC-based binary solvents of EC:DEC, EC:DMC, and EC:PC on the reversibility is negligible for the PANa electrode during 100 cycles as confirmed by Figure S10, but 1.0 mol dm -3 KFSA/PC results in continuous electrolyte decomposition at 0.7 V vs. K (equal to 0.8 V vs. Li), which is likely due to co-intercalation of PC-solvated K + ions and/or dissolution of SEI components, leading to graphite exfoliation and electrolyte decomposition 24 similar to Li|LiClO4-PC|graphite cell. [30][31][32] Thus, we selected an electrolyte of 1.0 mol dm -3 KFSA/EC:DEC for the subsequent studies.…”
Section: Electrochemical Propertiesmentioning
confidence: 76%
“…According to Zhang's 24 and our reports, 13,25 selection of potassium electrolyte salts significantly affects reversible capacities, Coulombic efficiency, and cycle stability of the graphite electrode in a K cell. Using PVdF as a binder for the graphite electrodes, we confirmed that the highest Coulombic efficiency and the superior cycle stability are obtained in 1.0 mol dm -3 KFSA/EC:DEC (1:1 v/v) electrolyte compared to those in 0.8 mol dm -3 KPF6/EC:DEC or 1.0 mol dm -3 KTFSA/EC:DEC as shown in Figure S2.…”
Section: Electrochemical Propertiesmentioning
confidence: 97%
“… 114 With a specially designed electrolyte, Ming et al improved the areal capacity of graphite anode from 0.2 to 0.5 mA h cm −2 . 181 At this stage, the areal capacity is far from that of conventional LIBs, and unique material engineering and rational electrode design are still required.…”
Section: Current Main Challengesmentioning
confidence: 99%
“…The overall trend of the structural phase transition is consistent with previous reports. 16,[26][27][28][29][30] When comparing details of the two graphite samples, one can see a distinct difference in peak positions during the phase transition between stage-2 and stage-1 (see selected offset-free XRD patterns in Fig. S6 and enlarged patterns in Fig.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…3 to reversibly transforms back into graphite by potassium deintercalation. 16,[26][27][28]30 However, both the graphite electrodes after depotassiation at the 1 st cycle displayed not only a sharp diffraction peak of graphite but also broad peaks of residual K-GIC as shown in Fig. S8.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%